2016
DOI: 10.1902/jop.2016.160214
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Local Antimicrobials in the Non‐Surgical Treatment of Patients With Periodontitis and Diabetes: A Systematic Review

Abstract: In patients with DM and CP, use of local antimicrobials as an adjunct to SRP may result in additional benefits compared with SRP alone in PD reduction and CAL gain, especially in well-controlled individuals and deep sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 38 publications
0
26
0
2
Order By: Relevance
“…Local antimicrobials have been evaluated, for the treatment of periodontitis, in systematic reviews and randomized controlled trials (Table ) . Periodontal pocket depth reduction beyond that obtained by scaling alone may vary from 0.4 mm to 0.6 mm , and additional clinical attachment gain of up to 0.3 mm may be achieved .…”
Section: Adjunctive Pharmacological Therapymentioning
confidence: 99%
“…Local antimicrobials have been evaluated, for the treatment of periodontitis, in systematic reviews and randomized controlled trials (Table ) . Periodontal pocket depth reduction beyond that obtained by scaling alone may vary from 0.4 mm to 0.6 mm , and additional clinical attachment gain of up to 0.3 mm may be achieved .…”
Section: Adjunctive Pharmacological Therapymentioning
confidence: 99%
“…As a result of the severity of periodontal disease in diabetic patients, some clinical studies have evaluated the adjunctive effect of antibiotics in nonsurgical periodontal treatment for these patients. A recent systematic review (SR) has shown that local antimicrobials are effective in reducing probing pocket depth (PPD) and increasing clinical attachment level (CAL) in diabetic patients. Two recent SRs have addressed the effect of systemic antimicrobials in diabetic patients with periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Although a wide array of therapeutic entities are available, these predominantly possess antibiotic, antimicrobial or anti-inflammatory properties, thereby indirectly promoting periodontal healing through the eradication of dental plaque/bacterial biofilm accumulation and/or the exacerbation of chronic inflammatory responses [ 8 , 37 ]. Furthermore, despite the development of a plethora of antibiotic and non-antibiotic-based drug delivery approaches to counteract microbial accumulation, biofilm formation or the inflammation associated with periodontal disease, few agents have fully progressed to routine clinical use [ 38 , 39 ]. Thus, in addition to addressing the side effects commonly associated with such therapeutics, the development of efficacious pharmaceutical options with established potent antimicrobial, anti-inflammatory and pro-healing properties, such as pomegranate, could meet a significant clinical and public health need in reducing the prevalence and severity of such conditions on a global scale.…”
Section: Discussionmentioning
confidence: 99%